HIV-1 replication and immune dynamics are affected by raltegravir intensification of HAART-suppressed subjects - J Buzón, Maria; Massanella, Marta; Llibre, Josep M; Esteve, Anna; Dahl, Viktor; Puertas, Maria C; Gatell, Josep M; Domingo, Pere; Paredes, Roger; Sharkey, Mark; Palmer, Sarah; Stevenson, Mario; et al. (Nature medicine, 2010)
Despite highly active antiretroviral therapy, active replication persists and drives immune activation in some individuals with HIV. This activation is higher if therapy is intensified by additional antiretroviral drugs ( pages 373–374 ). Highly active antiretroviral therapy (HAART) results in potent and durable suppression of HIV-1 viremia. However, HIV-1 replication resumes if therapy is interrupted 1 , 2 . Although it is generally believed that active replication has been halted in individuals on HAART, immune activation and inflammation continue at abnormal levels 3 , suggesting continued, low-level viral replication. To assess whether active replication might be driving immune activation in HAART, we examined the impact of treatment intensification with the integrase inhibitor raltegravir on viral complementary DNA and immune activation parameters. In the presence of raltegravir, linear HIV-1 cDNA is prevented from integrating into chromatin and is subsequently converted to episomal cDNAs 4 , 5 . Raltegravir intensification of a three-drug suppressive HAART regimen resulted in a specific and transient increase in episomal DNAs in a large percentage of HAART-suppressed subjects. Furthermore, in subjects with these episomal DNAs, immune activation was higher at baseline and was subsequently normalized after raltegravir intensification. These results suggest that, despite suppressive HAART, active replication persists in some infected individuals and drives immune activation. The ability of raltegravir intensification to perturb the reservoir that supports active replication has implications for therapeutic strategies aimed at achieving viral eradication.